2004
DOI: 10.1136/hrt.2003.023630
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular aneurysm secondary to sarcoid disease

Abstract: T he long held belief that coronary heart disease (CHD) in women has a more benign prognosis than in men has resulted in less aggressive diagnosis and management patterns. Contrary to this belief, CHD is the leading cause of death in white women aged 60 years or older in the USA and outnumbers the next 16 causes of death in women combined, including cancers. Furthermore, since 1980, death from CHD has declined dramatically in men in the western world but has increased in women. 1With the recent recognition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…229 Accordingly, echocardiography, cardiac CT, cardiac MRI and contrast left ventriculography may be used in the diagnosis of cardiac sarcoidosis (Figure 32). 190,[230][231][232][233][234] Left ventricular aneurysm without coronary artery disease should be examined to rule out hypertrophic cardiomyopathy, Chagas disease, arrhythmogenic right ventricular cardiomyopathy, chronic myocarditis, glycogen storage disease and idiopathic left ventricular aneurysm. 235 Left ventricular aneurysm in cardiac sarcoidosis is an important finding as it has been reported that the presence of ventricular aneurysm predicts poor clinical outcome in cardiac sarcoidosis.…”
Section: ▋ 28 Cardiac Catheterization ▋ 281 Contrast Left Ventricumentioning
confidence: 99%
“…229 Accordingly, echocardiography, cardiac CT, cardiac MRI and contrast left ventriculography may be used in the diagnosis of cardiac sarcoidosis (Figure 32). 190,[230][231][232][233][234] Left ventricular aneurysm without coronary artery disease should be examined to rule out hypertrophic cardiomyopathy, Chagas disease, arrhythmogenic right ventricular cardiomyopathy, chronic myocarditis, glycogen storage disease and idiopathic left ventricular aneurysm. 235 Left ventricular aneurysm in cardiac sarcoidosis is an important finding as it has been reported that the presence of ventricular aneurysm predicts poor clinical outcome in cardiac sarcoidosis.…”
Section: ▋ 28 Cardiac Catheterization ▋ 281 Contrast Left Ventricumentioning
confidence: 99%
“…Even though the pathogenesis of MA associated with sarcoidosis has not been defi ned clearly, many reports describe ventricular aneurysms in association with cardiac sarcoidosis [11][12][13] and abdominal aortic aneurysms complicating sarcoidosis. 14,15 Retinal MA is likely to have the same etiology as systemic vascular disorders.…”
Section: Discussionmentioning
confidence: 98%
“…When thoracotomy is performed for evacuation and biopsies, the liquid is mostly serosanguineous [45]. Arrhythmias, cardiac insuffiency, sudden death can be due to ventricular aneurysm [27,29,[89][90][91][92][93]. This left or right aneurysm presents with a variable size, arises rather quickly before steroid therapy and is often associated to cardiomyopathy [89,90,93].…”
Section: Boxmentioning
confidence: 99%